Patient preference for early onset of efficacy of preventive migraine treatments. Issue 3 (20th February 2022) - Ailani, Jessica; Winner, Paul; Hartry, Ann; Brevig, Thomas; Bøg, Martin; Lassen, Anders Blædel; Marsh, Kevin; Cutts, Katelyn; Le Lay, Agathe
Abstract: Objective: The objective of this study was to ascertain to what extent adults with migraine value an early onset of efficacy for preventive migraine treatments. Background: In placebo‐controlled clinical trials, treatment with eptinezumab resulted in a lower proportion of adults with migraine on the first day following infusion (day 1; 14% point‐reduction for chronic migraine [CM] in PROMISE‐2 and 8% point‐reduction for episodic migraine [EM] in PROMISE‐1). Methods: Adults with migraine completed an online preference‐elicitation thresholding exercise to ascertain to what extent they value not having a migraine on day 1 postdosing relative to a clinically relevant reduction in number of migraine days during the first month postdosing (≥2 migraine‐free days for CM and ≥1 migraine‐free days for EM). Results: One hundred and one participants (mean age, 50.6 ± 12.4 years; 81 [80%] women) were included. In participants with CM, 29 of 50 (58%) considered the eptinezumab‐generated reduction in the likelihood of migraine on day 1 postdosing to be at least as important as a clinically relevant reduction in number of migraine days the first month postdosing, whereas 37 of 50 (74%) considered a clinically relevant reduction of migraine days the first month postdosing to have a value equivalent to the eptinezumab‐generated reduction in the likelihood of migraine on day 1 postdosing. In participants with EM, 18 of 35 (51%) considered the eptinezumab‐generated reduction in the likelihood of migraine on day 1 postdosing to be at least as important as a clinically relevant reduction in migraine days the first month postdosing, whereas 24 of 35 (69%) considered a clinically relevant reduction of migraine days the first month postdosing to have a value equivalent to the eptinezumab‐generated reduction in the likelihood of migraine on day 1 postdosing. Conclusion: Most participants considered the reduction in the likelihood of migraine offered by eptinezumab on day 1 postdosing to be at least as important as a clinically relevant reduction in migraine days the first month postdosing.